Green Product: Snack Food Non-Plastic Sebagai Mediasi Minat Beli Gen Z - Sopingi, Imam; Haryanti, Peni; Santoso, Rohmad Prio (Universitas Hamzanwadi, 2024)
The purpose of this study was to survey the influence of environmental awareness, quality, price, and product brand image on Generation Z's purchase intention, with non-plastic snack food as the mediation. The method used is a survey of SMA/SMK/MA students in five districts: Jombang, Kediri City, Kediri Regency, Tulungagung, and Trenggalek, using purposive sampling technique for respondents who have or will buy snacks without plastic packaging, a total of 352 have filled it out. The results state that environmental awareness, product quality and brand image have no direct effect on purchase intention, while price does. Indirectly, all variables affect purchase intention intervened by non-plastic snack food, except product quality. This shows that respondents pay more attention to price, brand image and environmental awareness regarding non-plastic goods. The implication of this research is important for producers in designing marketing strategies that consider these factors to attract Generation Z buying interest.